1998 Proceedings. 48th Electronic Components and Technology Conference (Cat. No.98CH36206) 1998
DOI: 10.1109/ectc.1998.678929
|View full text |Cite
|
Sign up to set email alerts
|

O/e-MCM packaging with new, patternable dielectric and optical materials

Abstract: This paper presents a novel ole-MCM-LID-concept for fully integrated opto-electronic MCM-packaging aiming at: very low cost, very high interconnect density and high performance. The polymer thin film materials technology allowing the integration of optical waveguides and high density electrical interconnects in just 3 thin film layers is also discussed in terms of chemistry, processes and properties. Very good processability and planarization of the new inorganic-organic photo-polymers, ORMOCERs, (ORganically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…4): this increase is restricted in the industrial range of frequency but becomes relevant at frequencies below 10 Hz. Even though the a.c. characterization of the coatings alone has not been performed in the present article, dielectrical characterizations carried out on coatings of similar composition17, 27 provided ε′ data around 3.5–4.0, at frequencies between 1 and 10 kHz, which is probably quite consistent with our results in the same frequency range. From the loss factor data (Fig.…”
Section: Resultssupporting
confidence: 90%
“…4): this increase is restricted in the industrial range of frequency but becomes relevant at frequencies below 10 Hz. Even though the a.c. characterization of the coatings alone has not been performed in the present article, dielectrical characterizations carried out on coatings of similar composition17, 27 provided ε′ data around 3.5–4.0, at frequencies between 1 and 10 kHz, which is probably quite consistent with our results in the same frequency range. From the loss factor data (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The flexibility of the approach, resulting from the large variety of available precursors and low synthesis temperature, offers the potential molecular engineering of both composition and properties for a wide range of solid materials. For optical applications, organic/inorganic hybrid materials have gained increased importance over the last decade, mainly due to their simplicity of preparation in the fabrication of photonic devices for the second and third telecommunication windows, located respectively at 1310 and 1550 nm [5][6][7][8][9]. However, the main factor limiting the development of such devices has been high propagation losses caused by absorption and scattering effects within the material.…”
mentioning
confidence: 99%
“…ORMOCERs have mostly been used as coating material [20], and in optical [21] and micro electronic applications [22]. In our own studies, we have also demonstrated the use of ORMOCOMP, a commercially available inorganicorganic hybrid polymer, as non-reflecting surfaces [23], as well as in different kinds of microfluidic applications such as in microchip capillary electrophoresis [24], surfaceassisted laser desorption ionization (SALDI) plates [25] and as oleophobic/oleophilic surface for adhesive self-assembly [26].…”
Section: Introductionmentioning
confidence: 78%